2019
DOI: 10.1159/000500311
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and Genotypic Characterization of ESBL-, AmpC-, and Carbapenemase-Producing <b><i>Klebsiella pneumoniae</i></b> and <b><i>Escherichia coli</i></b> Isolates

Abstract: Objectives: Drug resistance among gram-negative bacteria is a worldwide challenge. Due to the importance of drug-resistant Klebsiella pneumoniae and Escherichia coli strains in hospital-acquired infections, we aimed to determine the phenotypic and genotypic characteristics of ESBL-, AmpC-, and carbapenemase-producing isolates obtained from hospitalized patients in Tehran and Ilam (Iran). Materials and Methods: In total, 90 K. pneumoniae isolates and 65 E. coli isolates were collected from various infections. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
23
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 28 publications
11
23
2
Order By: Relevance
“…Several studies have reported that AmpC producer in K. pneumoniae ranged from 7.8% to 43%. [37][38][39] Similar to a previous study, resistance to carbapenem among Enterobacter spp. was high.…”
Section: Discussionsupporting
confidence: 78%
“…Several studies have reported that AmpC producer in K. pneumoniae ranged from 7.8% to 43%. [37][38][39] Similar to a previous study, resistance to carbapenem among Enterobacter spp. was high.…”
Section: Discussionsupporting
confidence: 78%
“…The relation between ERIC patterns and β-lactam resistance encoding genes profiles was studied where 42 different resistance gene profiles were distributed among 34 ERIC patterns that represent all tested K. pneumoniae isolates. Similar results were reported by Kazemian et al [51] Our results indicated the significance and convenience of ERIC-PCR and β-lactam resistance encoding genes profiles in differentiating isolates based on genetic relatedness. The diversity in our isolates represented a problem in the treatment of K. pneumoniae infections.…”
Section: Plos Onesupporting
confidence: 91%
“…Similar results were reported by Kazemian et al . [ 51 ] Our results indicated the significance and convenience of ERIC-PCR and β-lactam resistance encoding genes profiles in differentiating isolates based on genetic relatedness. The diversity in our isolates represented a problem in the treatment of K .…”
Section: Discussionmentioning
confidence: 73%
“…Reuland et al [28] described in their study pAmpC (bla CMY , bla MOX , bla FOX , bla DHA , bla ACT , bla MIR , and bla ACC ) in community strains in Amsterdam. Ribeiro et al [15] and Kazemian et al [29] identified bla DHA bla CMY and bla CIT pAmpC in Klebsiella pneumoniae, Escherichia coli, and Proteus mirabilis in different types of nosocomial infections in Portugal and Iran, respectively.…”
Section: Resultsmentioning
confidence: 99%